How do integrate function `int (3x^2)/e^(x^3) dx` ?

### 1 Answer | Add Yours

You need to evaluate indefinite integral `int (3x^2)/(e^(x^3)) dx` using substitution such that:

`x^3 = y =gt 3x^2 dx = dy`

You need to change the variable such that:

`int (dy)/(e^(y)) = int e^(-y) dy `

`int e^(-y) dy = -e^(-y)+ c`

You need to substitute `x^3` for `y` such that:

`int (3x^2)/(e^(x^3)) dx = -e^(-x^3) + c`

**Hence, evaluating the indefinite integral yields `int (3x^2)/(e^(x^3)) dx = -e^(-x^3) + c` **

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes